Tipologías de los procesos de producción agrícola frente a la diversificada demanda mercados y consumidores - Aguilar Gonzalez, Jordy Aaron (2021)
This research work deals with the different types of production in agricultural products in the face of the diversified demand of markets and consumers. Reference is made to the types of agriculture such as: conventional, conservationist, organic, ecological, agroecological, among others. Through data analysis, each of them is explained and it was concluded that the most used by humans in many cases is conventional agriculture, introduced with greater demand in the market, although its products are not as healthy due to the containment of chemical uses. On the other hand, small producers forge their crops based on organic, ecological and agroecological agriculture. These carry with them ecological and social values, they are cultivated with stricter standards to take care of the ecosystem giving a long-term environmental sustainability and harvesting a healthier product. In addition, it was emphasized that the prices of these are not fully profitable for the profitability of small producers. As for the wholesalers, they do have a better economy in their profits, due to the export of these agricultural products.